Features of acoustic emission during deformation of aluminum alloys with different types of strain behavior - Bashkov O. V.; Panin S. V. Sergey Viktorovich; Bashkova T. I.; Byakov A. V. Anton Viktorovich; Popkova A. A.; Shakirov I. V. (Научные основы разработки материалов с многоуровневой иерархической структурой, 2015)
Заглавие с экрана